Case report: Revealing a special and rare autoimmune GFAP astrocytopathy in the spinal cord succeeding Neurobrucellosis infection - He, Qiang; Liu, Junxian; Zhu, Zehua; Tang, Yongxiang; Long, Lili; Hu, Kai (Frontiers in Immunology, 2022)
Brucellosis, a zoonosis, can cause an inflammatory response in most organs and continues to be a public health problem in some endemic areas, whereas neurobrucellosis is a morbid form of brucellosis that affects the central nervous system (CNS) with poor prognosis. Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy is an autoimmune disease and there have been no reports of Brucella infection leading to GFAP astrocytopathy. We report the case of a patient with positive and high level of GFAP antibodies in the cerebrospinal fluid (CSF) following Brucella infection. Although this patient did not show any responsible lesions in the diffusion sequence of the magnetic resonant imaging (MRI) scan, we found evidence of thoracolumbar (T12) involvement on FDG PET. The symptoms of spinal cord involvement were only partly relieved after initial treatment (doxycycline (0.1 g Bid) and rifampicin (0.6 g Qd) for 6 weeks),however, they markedly improved after the subsequent immunosuppressive therapy (intravenous methylprednisolone (1000 mg for 3 days) followed by a 50% reduction from the preceding dose after 3 days, and subsequently oral prednisone tablets (60 mg/day) was started, which was then gradually tapered (reduced 10 mg/day every 1-2 weeks)). The positive response to immunosuppressive therapy and treatment outcome strongly indicated the presence of an autoimmune neurological disease probably triggered by some infectious factors. Therefore, our findings reveal Brucella infection is one of the causes of autoimmune GFAP astrocytopathy and when this infection is difficult to be identified by regular MRI, FDG PET can be used as a supplementary method for diagnosis and treatment.